Impact of donor coronary angiography on kidney transplantation outcomes. Issue 9 (9th August 2018) - Lesouhaitier, Mathieu; Legeai, Camille; Savoye, Emilie; Cantrelle, Christelle; Pipien, Isabelle; Macher, Marie‐Alice; Vigneau, Cécile; Dorent, Richard
Abstract: Coronary angiography (CA) is the gold standard evaluation of coronary artery disease in potential multi‐organ donors. This use of iodinated contrast media could lead to contrast‐induced acute kidney injury and consequently to delayed graft function (DGF). All patients in France who received a kidney from a 45‐70‐year‐old donor without medical contraindication for cardiac donation and with at least one cardiovascular risk factor were included. Recipients of preemptive kidney transplant or multi‐organ transplant, or who died within the first 8 days post‐transplantation were excluded. Data were obtained from CRISTAL database. From March 2012 to June 2014, 892 kidneys from 483 donors were transplanted. DGF was reported in 38.9% of the 375 kidney recipients grafted with a kidney from the 217 donors who had CA and in 45.5% of the 440 kidney recipients who received a kidney from the 257 donors without CA. Multivariate analysis showed that CA or repeated injection of iodinated contrast media did not influence the risk of DGF. CA did not increase the risk of primary non‐function, the duration of DGF or post‐transplantation hospital stay and did not affect the graft function at 1 year. Evaluation of potential multi‐organ donors with CA does not affect kidney graft outcomes.